Implementation of corneal confocal microscopy for screening and early detection of diabetic neuropathy in primary care alongside retinopathy screening: Results from a feasibility study - Carmichael, Josie; Fadavi, Hassan; Ishibashi, Fukashi; Howard, Susan; Boulton, Andrew J. M.; Shore, Angela C.; Tavakoli, Mitra (Frontiers in Endocrinology, 2022)
ABSTRACT Objective: Screening for diabetic peripheral neuropathy (DPN) is essential for early detection and timely intervention. Quantitative assessment of small nerve fiber damage is key to the early diagnosis and assessment of its progression. Corneal confocal microscopy (CCM) is a non-invasive, in-vivo diagnostic technique that provides an accurate surrogate biomarker for small-fiber neuropathy. In this novel study for the first time, we introduced CCM to primary care as a screening tool for DPN alongside retinopathy screening, to assess the level of neuropathy in this novel cohort. Research Design and Methods: 450 consecutive subjects with type 1 or type 2 diabetes attending for annual eye screening in primary care optometry settings underwent assessment with CCM to establish the prevalence of sub-clinical diabetic neuropathy. Subjects underwent assessment for neurological and ocular symptoms of diabetes and a history of diabetic foot disease, neuropathy, and retinopathy. Results: CCM examination was completed successfully in 427 (94.9%) subjects, 22% of whom had neuropathy according to Diabetic neuropathy symptom (DNS) score. The prevalence of sub-clinical neuropathy as defined by abnormal corneal nerve fiber length (CNFL) was 12.9%. In the subjects with a short duration of type 2 diabetes, 9.2% had abnormal CNFL. CCM showed significant abnormalities in corneal nerve parameters in this cohort of subjects with reduction of CNFD (p<0.001), CNFL (p<0.001), and CNBD (p<0.001) compared to healthy subjects. In subjects who had no evidence of DR (67% of all subjects), 12.0% had abnormal CNFL. Conclusions: CCM may be a sensitive biomarker for early detection and screening of DPN in primary care alongside retinopathy screening.